2010
DOI: 10.1021/bi901764m
|View full text |Cite
|
Sign up to set email alerts
|

Scherffelia dubia Centrin Exhibits a Specific Mechanism for Ca2+-Controlled Target Binding

Abstract: Centrins are calcium binding proteins that belong to the EF-hand (or calmodulin) superfamily, which are highly conserved among eukaryotes. Herein, we report the molecular features and binding properties of the green alga Scherffelia dubia centrin (SdCen), a member of the Chlamydomonas reinhardtii centrin (CrCen) subfamily. The Ca(2+) binding capacity of SdCen and its isolated N- and C-terminal domains (N-SdCen and C-SdCen, respectively) was investigated using flow dialysis and isothermal titration calorimetry.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 64 publications
3
23
0
Order By: Relevance
“…The ITC experiments presented here and in previous work demonstrated that the affinity of centrin is better for XPC than for other targets such as Sfi1 [22,25,30] and transducin β [Grecu and Assairi to be published elsewhere]. This could suggest that the orientation of the centrin‐binding motif of XPC is the best orientation for effective centrin binding.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The ITC experiments presented here and in previous work demonstrated that the affinity of centrin is better for XPC than for other targets such as Sfi1 [22,25,30] and transducin β [Grecu and Assairi to be published elsewhere]. This could suggest that the orientation of the centrin‐binding motif of XPC is the best orientation for effective centrin binding.…”
Section: Discussionsupporting
confidence: 60%
“…Experiments using microcalorimetry have demonstrated that the C‐terminal domain of centrin is sufficient for target binding. However, for algal centrins, the N‐terminal domain also binds targets, but only in the presence of calcium [21,22]. The structures of the N‐terminal domain of C. reinhardtii [21] and human centrins have been solved by NMR [23].…”
Section: Introductionmentioning
confidence: 99%
“…In general, the C-terminal domain of centrin is able to bind target peptides in a Ca 2+ -independent manner (Li et al 2006;Radu et al 2010;Veeraraghavan et al 2002) and is often important for the subcellular localization of centrin protein (Gavet et al 2003;Li et al 2006;Vonderfecht et al 2011), whereas the N-terminal domain typically binds Ca 2+ and target peptides with lower affinity (Li et al 2006; Thompson et al 2006;Veeraraghavan et al 2002;Yang et al 2006) and plays indispensable roles different from the Cterminal domain (Ivanovska and Rose 2001;Vonderfecht et al 2011). Compared to calmodulins, most centrins possess an extension of variable-length N-terminal to the EF hand motifs (Friedberg 2006;Salisbury 1995).…”
Section: Overview Of Centrinsmentioning
confidence: 99%
“…Goedhart and Gadella 2004;, gravity sensing and polarized growth (e.g. Braun and Limbach 2005;Braun and Limbach 2006), exudates secretion (Quesada et al 2006), action potential generation (Beilby 2007) and binding to calcium-binding proteins, for example the basal body connector associated protein centrin (Radu et al 2010). There are very few publications for touch-induced calcium signaling in algae.…”
Section: The Bioluminescent System Of Pyrocystis Lunulamentioning
confidence: 99%